SPORTS FOR ALL MOVEMENT: FROM OPPOSING HIGH LEVEL PERFORMANCE SPORTS TO PROMOTING CURRENT HEALTH (Fiep Bulletin - online, 2012)
Sports for All Movement was one of the most effective manifestations in Physical Education and Sportsin the 20th century. Since it was created in Norway in the 1960s, Sports for All Movement has spread throughoutthe world. Conferences and meeting were held in West Germany (1967 and 1970), in Norway (1969), in Holland(1971) and in Buenos Aires (1973), where Sports for All was one of the sessions in the “Jornadas Internacionaisde Estudio sobre el Deporte”.The first goal to be achieved by Sports for All Movement was the democratization of the sports practices.This goal was achieved by UNESCO's International Charter of Physical Education and Sport. The Sports for AllMovement was incorporated to the manifestations of Leisure-Sports, mainly for its characteristics andspontaneity.Having been conceived from a viewpoint that envisions the democratization of sports practices, Sportsfor All Movement has become the most efficient means for Leisure-Sports, and in the end of the 20th century it hasincorporated the health promotion goals to its purposes and contents.